Evolution of concept of esophageal motor disturbances in pathogenesis of gastroesophageal reflux disease - V. T. Ivashkin; A. S. Trukhmanov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2010)
The aim of publication. To present up-to-date data on the role of disorders of motor function of the esophagus in development of gastroesophageal reflux disease and mechanisms of transient lower esophageal sphincter relaxations (TLESR) on functional activity of antireflux barrier.Original positions. There are several components of TLESR mechanism: decrease of the lower esophageal sphincter pressure, modulated by inhibiting impulses; decrease of compression by crures of diaphragm; intensive contraction of longitudinal muscles of the esophagus; relaxation of circular musculature layer at its distal part. There are differences in TLESR mechanism between healthy persons and patients with gastroesophageal reflux disease (GERD) i.e.: at healthy subjects only gas enters the esophagus from the stomach during TLESR in contrast to patients with reflux disease. Obesity increases potential of TLESR appearance, associated with reflux of liquid contents from the stomach.Conclusion. Taking into account comprehension of available regulatory parts, reality of influence on esophageal motility and especially LES is tempting. Studying of this function opens encouraging prospects of improvement of treatment of GERD.